2003
DOI: 10.1046/j.1365-8711.2003.06281.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy voids in cold dark matter universes

Abstract: We present predictions for numerous statistics related to the presence of voids in the distribution of galaxies in a cold dark matter model of structure formation using a semi-analytic model of galaxy formation. Our study is able to probe galaxies with masses as low as 10 9 h −1 M corresponding to absolute magnitudes of M b J − 5 log h = −18.1 and M r − 5 log h = −18.7. We quantify the void and underdense probability functions, distributions of nearest-neighbour distances and void sizes and compute the density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
105
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 38 publications
(65 reference statements)
22
105
0
Order By: Relevance
“…These trends are generally consistent with predictions of semi-analytic modelling of galaxy formation (Benson et al 2003).…”
Section: Void Galaxy Propertiessupporting
confidence: 86%
“…These trends are generally consistent with predictions of semi-analytic modelling of galaxy formation (Benson et al 2003).…”
Section: Void Galaxy Propertiessupporting
confidence: 86%
“…4 However, Ref. 46 showed that these effects would not explain the distribution of dwarf galaxies in voids.…”
Section: 46107mentioning
confidence: 99%
“…Observations (Plionis & Basilakos 2002;Hoyle & Vogeley 2002Tully et al 2008;Tikhonov & Karachentsev 2006;Kraan-Korteweg et al 2008;Pan et al 2012;Sutter et al 2012) and N -body simulations (Regos & Geller 1991;van de Weygaert & van Kampen 1993;Dubinski et al 1993;Benson et al 2003;Gottlöber et al 2003;Colberg et al 2005;Tinker & Conroy 2009;Aragon-Calvo & Szalay 2013;Bos et al 2012;Ricciardelli et al 2013) show that voids can have sizes in the range 5 − 135h −1 M pc. There are voids that possess sizes smaller than this range; on the basis of the Catalog of Neighbouring Galaxies (Karachentsev et al 2004), Tikhonov & Karachentsev (2006) found 30 minivoids with a range of sizes, 0.7 − 3.5h −1 M pc.…”
Section: Introductionmentioning
confidence: 98%